Analyzing items used in developing descriptive essay marking rubrics : Focussing on vocabulary use - Mariann Edwina Mariadass,; Mohd Hasrul Kamarulzaman,; Yokana Veliapandian, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Descriptive writing is an excellent language learning strategy to improve students’ vocabulary and ultimately their language competence. Teachers have found that longer time is required to develop students’ descriptive writing skills, and it gets more complex because there is not many appropriate, or rather standardized, guideline to help teachers teaching descriptive writing. Most commonly, teachers employ the five-paragraph-writing format to teach writing. It was found in this study that students focus on vocabulary in describing scenes, characters, plots, or settings. Consequently, it is the aim of this study to explore the criteria or items of the existing rubrics used in descriptive writing, and develop an exclusive one that emphasizes on vocabulary. 20 prominent rubrics for descriptive writing were gathered and analyzed. Summative content analysis method was employed for the analysis. The most frequent components used were listed down and integrated into a new rubric. The findings revealed that there are several components used to assess descriptive writing namely description, word choice, and vocabulary competence. This study also found that with a specific descriptive writing rubric, teachers are able to better prepare their lessons in teaching descriptive writing. The exclusive descriptive writing rubric also helps students to better learn and develop their vocabulary.